An Integrated SQA Framework for e-Collaboration - Subramanian, T.; Rao, G.S.V.R. Krishna; Seetharaman, A. (2007)
In order to be effective and efficient, e-Collaboration applications frequently need to interact with numerous other applications, many of these applications may be within the same firm - intranet; some of them might be another participating firm's application - extranet. Service Oriented Approach is expected to provide solution to this issue and many organizations are undertaking SOA deployment but most of these implementations result in sub-optimal, due to lack of proper framework. Keeping the above as the research issue, this study aims to facilitate the development of framework which will help efficient management of the services in a service-oriented environment so as to allow business to rapidly develop, integrate and reuse applications in order to deliver dynamic solutions as e-collaboration needs evolve.